Time-of-Day and Age Impact on Memory in Elevated Plus-Maze Test in Rats - Morales-Delgado, Nicanor; Popović, Natalija; De la Cruz-Sánchez, Ernesto; Caballero Bleda, María; Popović, Miroljub (Frontiers in Behavioral Neuroscience, 2018)
The purpose of the present study was to establish the effect of daytime and aging on memory in rats in the elevated plus-maze test. Young (2-months) and aged (18-months) male Wistar rats were exposed to the elevated plus-maze test, at the beginning, mid-time or at the end of the light period. On the acquisition trial, the animals were placed individually at the end of one of the open arms of the elevated plus-maze and the latency to enter in the enclosed arms was registered (cut-off time 60 s). The test was repeated 24h later on. A longer latency period to reach the enclosed arm indicated poor retention compared to signiﬁcantly shorter latencies. There were no significant differences between groups on the acquisition trial. In all tested periods, the latency time on the 24h retention trial was significantly shorter in the young rats compared to the old ones. Furthermore, in the early and mid-time period of the light period, the young rats showed significantly decreased transfer latency time on the 24h retention trial in comparison with the acquisition trial. In the aged rats, the transfer latency time on the 24h retention trial was significantly longer at the end of the light period, in comparison to the two other testing periods. In conclusion, aging significantly affects memory and the more critical period for memory process in both young and old animals, particularly at the end of the light period of the circadian cycle.